2020
DOI: 10.1136/bmj.m2200
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus persistence and reactivation

Abstract: Hepatitis B virus (HBV) infection causes chronic hepatitis and has long term complications. Individuals ever infected with HBV are at risk of viral reactivation under certain circumstances. This review summarizes studies on HBV persistence and reactivation with a focus on the definitions and mechanisms. Emphasis is placed on the interplay between HBV replication and host immunity as this interplay determines the patterns of persistence following viral acquisition. Chronic infections exhibit as overt persistenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
101
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 202 publications
(319 reference statements)
1
101
0
2
Order By: Relevance
“…As a type of DNA molecule, circular DNA is ubiquitous in nature and includes bacterial plasmids as well as some viral genomes [ 1 3 ]. More than half a century ago, researchers found that there is also a special class of circular DNA in eukaryotes, which is isolated from the normal genome, free from the chromosomal genome and participates in physiological or pathological processes in special ways [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a type of DNA molecule, circular DNA is ubiquitous in nature and includes bacterial plasmids as well as some viral genomes [ 1 3 ]. More than half a century ago, researchers found that there is also a special class of circular DNA in eukaryotes, which is isolated from the normal genome, free from the chromosomal genome and participates in physiological or pathological processes in special ways [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic hepatitis B virus (HBV) infection remains a major global health burden, with 350 million chronically infected individuals worldwide (1,2). In addition to hepatocellular carcinoma (HCC) and decompensated cirrhosis, acute-onchronic liver failure (ACLF) is another cause of death in patients with chronic HBV infection (3).…”
Section: Introductionmentioning
confidence: 99%
“…Virus replication may return to normal levels at any time after drug withdrawal or drug resistance occurs ( Zoulim and Locarnini, 2009 ; Deng and Tang, 2011 ). cccDNA serves as a template for the transcription of viral RNAs through employing the cellular transcription machinery ( Rall et al, 1983 ; Shi and Zheng, 2020 ), which is resistant to common antiviral therapies. The key challenge is the persistence of cccDNA in infected hepatocytes.…”
Section: Introductionmentioning
confidence: 99%